PENDAMPINGAN LINKED PRODUK LOKAL MASYARAKAT DAN BUMDES - Firda Ayu Amalia; Thoufan Nur (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2022)
Petungsewu Village is one of the villages located in the Dau sub-district, Malang Regency. Petungsewu Village is a village that has superior citrus products and is a contributor most significant citrus production in East Java. The village community manages several owned businesses, but the home-based business has not been linked to BUMDes, owned by Petungsewu Village. In addition, the proportion of BUMDes in Petungsewu village that is actively operating is smaller than the BUMDes that are actively producing. The unlinked home-owned business owned by the community with BUMDes is one of the causes of economic growth. However, the improvement of community welfare has not been able to develop rapidly. The first problem that partners complained about to the service team was related to the unlinked business owned by the community and the BUMDes owned by the village. The second problem relates to the fact that there are still many BUMDes that are not yet actively operating, so the economic potential of Petungsewu village has not been maximized in the welfare of the community. Based on the two problems partners face, the service team provides a solution by linking or connecting owned businesses managed by each community and BUMDes to offer solutions to the first problem. Furthermore, the service team will reactivate BUMDes that are not yet actively operating. The method used to implement the first solution is to conduct FGD by inviting several representatives of owned business owners, BUMDes managers and representatives of village officials. Furthermore, the service team will use the solution to the second problem to carry out socialization and assistance. The service team invited all BUMDes managers, DPMD representatives and village officials in this activity.